1-(2-Hydroxyethyl)-2-imidazolidinone as corrosion inhibitor of mild steel in 0.5 M HCl solution: thermodynamic, electrochemical and theoretical studies. Issue 18 (17th September 2019) - Keleşoğlu, Ayşen; Yıldız, Reşit; Dehri, İlyas
Abstract: The inhibition effect of 1-(2-Hydroxyethyl)-2-imidazolidinone( 2-HEI) on mild steel (MS) corrosion in 0.5 M HCl solution was investigated at different inhibitor concentration and temperature by electrochemical experiments, such as linear polarization resistance (LPR), electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and quantum chemical calculations. The inhibitor adsorption process on mild steel in 0.5 M HCl system was studied at different temperatures (20 °C–50 °C). Furthermore, the surface morphology of MS was also investigated with SEM in the absence and the presence of inhibitor. The adsorption of 1-(2-Hydroxyethyl)-2-imidazolidinone on MS surface is an exothermic process and this process obeys the Langmuir adsorption isotherm. The Quantum chemical findings are good agreed with the empirical data.